Scleral Buckling with Viscoelastics or Gas Injection for Bulging Retinal Detachments: A Retrospective Cohort Study - Quan-Yong Yi; Wen-Die Li; Qian Gui; Sang-Sang Wang; Li-Shuang Chen; Jing-Hai Mao; Yan Gong; Xia-Jun Wang (Journal of Ophthalmology)
Objective. To examine the use of a viscoelastic agent instead of air in the vitreous cavity during surgery for scleral buckling. Methods. This was a retrospective cohort study of patients who underwent scleral buckling surgery for bulging rhegmatogenous retinal detachment (RRD) at Ningbo Eye Hospital from 07/2016 to 12/2019. The patients were grouped into drainage, air injection, cryotherapy and explant (DACE) and drainage, viscoelastic injection, cryotherapy, and explant (DVCE) groups, which were comparatively assessed. Results. There were 25 and 22 patients in the DVCE and DACE groups, respectively. The surgery was significantly shorter with DVCE than DACE (P<0.05), with less intraoperative external pressure adjustment (P<0.05). BCVA was lower in the DVCE group at 1 week compared with the DACE group (P<0.05). Successful retinal reattachment was observed in 92.0% and 81.8% of the DVCE and DACE groups, respectively (P<0.05). Cases requiring laser replenishing after the operation were less in the DVCE group compared with the DACE group (P<0.05). There were no differences in complications and intraocular pressure between the two groups (all P<0.05). Conclusion. DVCE has better operative characteristics and faster vision recovery than DACE, with similar outcomes.